A Analysis of Improving Student Learning Outcomes Class VIII A Kendari 5 Kendari Middle School in PPKn Lessons Through Teach Teaching Team - yuniar spenli (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2020)
Character-based education is a holistic process carried out to develop children’s academic capability and personality through which they eventually adopt wisdom and responsibility. The implementation of spoken tradition in social science learning, to This study aims to describe the improvement in the learning achievement of students of VIII A SMP Negeri 5 Kendari in PPKn learning through the application of team teaching. This research was conducted at SMP Negeri 5 Kendari. The research subjects were grade VIII A students, totaling 36 students, including 19 girls and 17 boys. Based on the results of research in two learning cycles: (1) the results of 10 aspects of observing student activity in the learning process with a total score of 27 with a value of 90.9 in the second cycle, there was an increase in value when compared to the first cycle a total score of 13 with a value of 43.3; (2) the results of 9 observation aspects of team teaching activities in learning with a total score of 24 with a value of 88.9 in the second cycle, an increase in value compared to the first cycle with a total score of 17 with a value of 62.9; and (3) the learning achievement achieved by students showed a very significant increase, wherein the second cycle there was an increase in the value of student learning outcomes with a class average of 81.11 and 30 students who obtained Indonesian scores ≥ 65 (83.33). %), there was an increase in value when compared to the first cycle where the value of student learning outcomes with a class average of 65.83 and students who obtained a PPKn value ≥ 65 were 19 students (52.78%). The application of team teaching in Indonesian language learning can improve the learning outcomes of grade VIII A students of SMP Negeri 5 Kendari.